Recent Developments in Fluorescent Materials for Heavy Metal Ions Analysis From the Perspective of Forensic Chemistry - Lian, Jie; Xu, Qiang; Wang, Yipeng; Meng, Fanda (Frontiers in Chemistry, 2020)
Forensic chemistry deals with the analysis of various types of physical evidences related to the crime, corresponding to the detection of target substances or elements in complex matrices. There is a vital need for highly selective, rapid and sensitive biosensing technologies in heavy metal ions analysis especially those from living persons, autopsy, food, water, soil and other identified substances at very preliminary stages. Fluorescent materials based method for heavy metal ions detection is one of the most important analytical methods, resulting in the ability to measure analytes in complex matrices with unsurpassed selectivity and sensitivity. In this mini review, different fluorescent materials based analytical methods aiming at several heavy metal ions detection are exclusively reviewed through a comprehensive literature survey. In addition, current challenges to achieve integrated evidence analysis process are briefly discussed to provide an outlook for heavy metal ions detection based on fluorescent analytical methods in the forensic chemistry field.